Validation of post‐traumatic stress disorder (PTSD) and complex PTSD using the International Trauma Questionnaire. (11th July 2017) - Hyland, P.; Shevlin, M.; Brewin, C. R.; Cloitre, M.; Downes, A. J.; Jumbe, S.; Karatzias, T.; Bisson, J. I.; Roberts, N. P.
Abstract : Objective: The 11th version of the International Classification of Diseases (ICD‐11) has proposed two related trauma diagnoses: Post‐traumatic stress disorder (PTSD) and Complex PTSD (CPTSD). Using a newly developed, disorder‐specific measure of PTSD and CPTSD called the International Trauma Questionnaire (ITQ) the current study will (i) assess the factorial validity of ICD‐11 PTSD and CPTSD; (ii) provide the first test of the discriminant validity of these constructs; and (iii) provide the first comparison of ICD‐11, and Diagnostic and Statistical Manual, Fifth Edition (DSM‐5), PTSD diagnostic rates using disorder‐specific measures. Method: ICD‐11 and DSM‐5 PTSD‐specific measures were completed by a British clinical sample of trauma‐exposed patients ( N = 171). The structure and validity of ICD‐11 PTSD and CPTSD were assessed by means of factor analysis and assessing relationships with criterion variables. Results: Diagnostic rates under ICD‐11 were significantly lower than those under DSM‐5. A two‐factor second‐order model reflecting the distinction between PTSD and CPTSD best represented the data from the ITQ; and the PTSD and CPTSD factors differentially predicted multiple psychological variables. Conclusion: The factorial and discriminant validity of ICD‐11 PTSD and CPTSD was supported, and ICD‐11 produces fewer diagnostic cases than DSM‐5.